2012
DOI: 10.1186/1751-0147-54-59
|View full text |Cite
|
Sign up to set email alerts
|

The stress signalling pathway nuclear factor E2-related factor 2 is activated in the liver of sows during lactation

Abstract: BackgroundIt has recently been shown that the lactation-induced inflammatory state in the liver of dairy cows is accompanied by activation of the nuclear factor E2-related factor 2 (Nrf2) pathway, which regulates the expression of antioxidant and cytoprotective genes and thereby protects tissues from inflammatory mediators and reactive oxygen species (ROS). The present study aimed to study whether the Nrf2 pathway is activated also in the liver of lactating sows.FindingsTranscript levels of known Nrf2 target g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 18 publications
1
14
0
1
Order By: Relevance
“…An inflammatory response and oxidative stress are detected in MS, and Nrf2 has been reported as being closely related to these inflammatory and oxidative stresses in the brain of MS patients (Gilgun-Sherki et al, 2004;Pöllinger et al, 2009;Johnson et al, 2010;Rosenbaum et al, 2012). In our EAE-modeled spinal cords, increased Nrf2 protein levels were again confirmed.…”
Section: Discussionsupporting
confidence: 71%
“…An inflammatory response and oxidative stress are detected in MS, and Nrf2 has been reported as being closely related to these inflammatory and oxidative stresses in the brain of MS patients (Gilgun-Sherki et al, 2004;Pöllinger et al, 2009;Johnson et al, 2010;Rosenbaum et al, 2012). In our EAE-modeled spinal cords, increased Nrf2 protein levels were again confirmed.…”
Section: Discussionsupporting
confidence: 71%
“…Recent studies have shown that lactation is another metabolic condition which is associated with the development of inflammation in the liver of pigs (Rosenbaum et al., ,b). It is likely that the induction of inflammation in the liver of lactating sows – which was also associated with the development of stress of the endoplasmic reticulum (ER stress), a condition triggered by inflammation – might be due to oxidative stress caused by the high metabolic activity or the occurrence of infectious diseases such as mastitis or metritis which are commonly observed in sows after parturition (Gessner et al., ,b).…”
Section: Consequences Of Inflammation On Performance Of Farm Animalsmentioning
confidence: 99%
“…Recent studies show that PD has obvious antioxidant property thought increasing the activities of superoxide dismutase (SOD) and catalase (CAT) [41, 42]. In fact, Nrf2 is an important regulator against oxidative stress, which increases the expression of HO-1, SOD, and CAT [43]. Thereby, we speculate that PD may be through the mechanism of Nrf2 activation to upregulation of HO-1.…”
Section: Discussionmentioning
confidence: 83%